Information Support for Socio-Economic Development Planning. (Part 2) Information Needs of Urban Planners - Neelameghan, A. (Journal of Information and Knowledge, 1996)
Part 2 of the series discusses the data and information needs of urban planning, using a case study from a developing country. Urban planning is an integral part of the overall planning for socio-economic development. It is inter- disciplinary and inter-sectorial. It involves decisions regarding the options that appear open for the future and then securing their implementation, with allocation of necessary resources, such as, human, finance, material, information, etc. It has, therefore, a strong political overtone as options need to be selected which may not benefit quitably all members of the society. Planning involves societal choice about the future which in tum implies political intervention. To exercise choice calls for genuinely alternative scenarios of the future. In order that choice from among possible of.action is purposeful and deliberate, a knowledge and understanding of the present and an explicit anticipation or foresight of future consequences of present actions are required. Such knowledge and understanding can be productive if appropriate data and information needed for each of the courses of action are accessible at the right time at reasonable cost and that they are reliable. precise and presented in conveniently usable forms. Different approaches to urban planning are discussed. Information and data required for effective urban planning, their sources. and output reports that may generally be useful to urban planners are presented in some detail.